A reverse-glass painting by Gerhard Janssen in the Valtice Palace - Míchalová, Zdeňka; Macurová, Zuzana (My University, 2024)
A previously unknown and unusually large seventeenth-century reverse-glass painting of St Philip’s baptism of the eunuch has been discovered in the Valtice Palace in the Czech Republic. Its artist is here identified as Gerhard Janssen, copying a print by Jan Gillisz. van Vliet after a lost painting by Rembrandt. It is probably a work recorded as being offered by Janssen to Prince Karl Eusebius of Liechtenstein in 1677.
Podmalba na skle od Gerharda Janssena na valtickém zámku
Keywords: reverse-glass painting; Gerhard Janssen, Rembrandt; Jan Gilisz van Vliet; 17th century painting; podmalba na skle; Gerhard Janssen, Rembrandt; Jan Gilisz van Vliet, malířství 17. století